The Definition of Enlightenment - Lighten up: My Use of Humor in Social Work Education and Practice - Rich Furman (Networks: An Online Journal for Teacher Research, 2002)
In this narrative, I discuss how humor has become a central "tool" of my practice as a social work educator and social worker. I describe how I use humor as a conscious means of achieving student learning. In a very real sense, calling humor a tool is a misnomer as it is a central feature of my personality. Each of us possesses certain personality characteristics that, if nurtured and cherished, can become powerful allies in the processes of teaching and helping.